Market Research: Yesterday, Today, Tomorrow - Алина Юрьевна Шанкина (Journal of Economic Sociology, 2010)
The paper analyzes the past, the present and the future of the marketing companies. The term of “market research” is discussed. The phenomenon of consumption is built into the cultural, historical and philosophical analysis.